UJI IRITASI MATERIAL COBALT CHROMIUM SEBAGAI MATERIAL DASAR BONE PLATE UNTUK REKONSTRUKSI MANDIBULA - Dian Permata Sari; Eti Nurwening Sholihah; Muhammad Kusumawan Herliansyah (Jurnal Teknosains, 2018)
The mandibular bone defect can cause speech disorder, mastication malfunction, and aesthetic problems. The application of plate for mandibular reconstruction can improve the function disorder. Plate material must be strong, resilient, able to adapt to the bone surface, and has good biocompatibility. Cobalt chromium is a cobalt base alloys are often used for implant materials. It has good mechanical properties, biocompatibility, and corrosion resistance. The aim of this study was to investigate the effect of local irritation and tissue response on material cobalt chromium. This study used three albino rabbits were injected by the material powder in polar and nonpolar solvents with intracutaneous injection method, then the treatments were observed on the first, second, and third days. Erythema and edema that occurs were scored based on grading system for intracutaneous (intradermal) reactions. Friedmann test showed no significant difference between treatment groups (p> 0.05). The results showed that erythema and edema arising from irritant reactions are still within normal limits. Irritation occurs due to the release of cobalt chromium ions which trigger hypersensitivity reactions and result in systemic immunity.